Situation Report: Poland, 2 May 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Gomulka Interview Gomulka's May 1 Speech Cardinal Wyszynski Not Going to Berlin Winiewicz on Economic Commission for Europe Polish Ambassador Saw Ball on Laos Commission Polish Ambassador in France on Oder-Neisse Line Polish-Chinese Trade Relations Further Trade News